Effect of spinning solvent on crystallization behavior of confined polymers in electrospun nanofibers. Issue 6 (22nd September 2021) - Pal, Sanchayan; Srivastava, Rajiv K.; Nandan, Bhanu
Abstract: The effect of spinning solvent on the morphology and crystallization behavior of the electrospun nanofibers of polystyrene (PS)/poly(ethylene oxide) (PEO) blends was investigated. The PS/PEO blends, with PEO as the minority component, were electrospun using binary solvent mixtures, involving DMF, dichloromethane and chloroform, with varying solvent dielectric constant and volatility. Even though the bulk morphology of the electrospun nanofibers broadly consisted of PEO domains dispersed in PS matrix, the size and dispersity of the PEO domains depended on the spinning solvent. The high dielectric constant and low volatility of DMF ensured higher jet stretch as well as longer available time for the break‐up of PEO domains, for solvent mixtures enriched in the DMF. This resulted in a notable influence on the crystallization behavior of PEO in the blend nanofibers. The fractionated behavior of PEO crystallization was observed to become more noticeable at high DMF content. This was due to the presence of relatively larger population of nanosized PEO domains in nanofibers where the crystallization occurred mostly due to homogenous nucleated crystallization. The present study highlights the role of spinning solvent on crystallization behavior in electrospun nanofibers of polymer mixtures which will ultimately also affect its other properties. Abstract : The dielectric constant and vapor pressure of the spinning solvent influenced the crystallization behavior of PEO, in PS/PEO blend electrospun nanofibers.